A framework for evaluating the implications of assumptions in broad conservation strategies. Issue 8 (5th July 2022) - Specht, Hannah; Golding, Jessie D.; Pero, Ellen M.; Crane, Madison T.; Ortiz‐Calo, Waldemar; McDevitt, Molly C.; Karlen, Jonathan G.; Branch, J. Vaughan; Hansen, Christopher P.; Millspaugh, Joshua J.
Abstract: Assumptions about how conservation practices will affect ecological outcomes are critical for informing and learning from conservation actions. However, when assumptions do not reflect conditions to which they are applied, they can impede achievement of targeted outcomes and hinder capacity to contribute to conservation goals. We assert that identifying and examining technical assumptions, or those that relate to abiotic or biotic systems, in conservation practice retrospectively for broad conservation strategies is crucial for advancing learning in conservation. Unlike existing proactive assumption frameworks, retroactive examination, which is often realistic for broad scale conservation, allows for honest evaluation of the contributions of those strategies toward shared goals. We propose the state, identify, focus, and think (SIFT) framework, a four‐step process, to guide examination of technical assumptions by defining how assumptions interact with biological circumstances to shape outcomes. We demonstrate use of the SIFT framework with a common technical assumption in US federal private lands conservation programs—that all acres are similarly valuable for achieving wildlife conservation benefits. With the SIFT framework, we show that the benefits of these programs are likely to be applicable to mobile, generalist species with small space requirements, while many species of conservation concern are less likely to benefit. Abstract : Assumptions aid in conservation when correctly applied. We propose a state, identify, focus, think framework to assess applied assumptions.